Pegaptanib sodium in treatment of wet AMD - Ulińska, Magdalena (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Taking into consideration that the advanced stage of Age related Macular Degeneration is a very common cause of social blindness and present results of laser photocoagulation, PDT treatment and TTT are not satisfying, it seems to be of huge importance to look for new types of treatment, to improve visual outcomes. Repeated intravitreal injection of pegaptanib sodium (a VEGF aptamer) is a modern procedure which may not only give stabilization of visual acuity, but it may also lead to the improvement in high percentage. In this paper there is a short update on the epidemiology and the symptoms of the disease and the role of VEGF and its isoforms expression in the development of wet AMD. The presentation of pegaptanib sodium (Macugen®) focus on its mechanism of action. Finally V.I.S.I.O.N. trial results are presented to show encouraging efficacy of the procedure.